Heidegger and ethics - Hodge, Joanna, 1953- (Routledge, 1995)
Heidegger and ethics is a contentious conjunction of terms. Martin Heidegger himself rejected the notion of ethics, while his endorsement of Nazism is widely seen as unethical. This major new study examines the complex and controversial issues involved in bringing them together. By working backwards through his work, from his 1964 claim that philosophy has been completed to Being and Time, his first major work, Joanna Hodge questions Heidegger's denial that his enquires were concerned with ethics. She discovers a form of ethics in Heidegger's thinking which elucidates his impor.